What Works in Conservation 2020 2020
DOI: 10.11647/obp.0191.04
|View full text |Cite
|
Sign up to set email alerts
|

4. Farmland Conservation

Abstract: Create ponds (amphibians in general) Create ponds (frogs) Create ponds (natterjack toads) Create ponds (salamanders including newts) Create wetlands Deepen, de-silt or re-profile ponds Restore wetlands Create ponds (great crested newts) Create ponds (green toads) Create ponds (toads) Remove specific aquatic plants Restore ponds Remove tree canopy to reduce pond shading Add nutrients to new ponds as larvae food source Add specific plants to aquatic habitats Add woody debris to ponds Create refuge areas in aquat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…One of the core issues that many grassland butterflies face is too many grass cuttings through the summers. Studies have shown that delayed mowing and delayed first grazing has outstandingly positive effects for the invertebrate, plant and bird species studied (Dicks et al, 2020). For that reason, inside the European Union there have been stimuluses to defer the farmers from mowing too often and restrict overgrazing to protect Natura 2000 species (European Commissions, 2018).…”
Section: Conservationmentioning
confidence: 99%
“…One of the core issues that many grassland butterflies face is too many grass cuttings through the summers. Studies have shown that delayed mowing and delayed first grazing has outstandingly positive effects for the invertebrate, plant and bird species studied (Dicks et al, 2020). For that reason, inside the European Union there have been stimuluses to defer the farmers from mowing too often and restrict overgrazing to protect Natura 2000 species (European Commissions, 2018).…”
Section: Conservationmentioning
confidence: 99%
“…One of the core issues that many grassland butterflies face is too many grass cuttings through the summers. Studies have shown that delayed mowing and delayed first grazing has outstandingly positive effects for the invertebrate, plant and bird species studied (Dicks et al, 2020). For that reason, inside the European Union there have been stimuluses to defer the farmers from mowing too often and restrict overgrazing to protect Natura 2000 species (European Commissions, 2018).…”
Section: Conservationmentioning
confidence: 99%
“…The abundance of butterflies, moths and some bumblebees is positively related to grass sward height and sward height variation (Milberg et al ., 2016), reflecting the role of grasses as larval host plants and grass swards as nesting sites. Resources are affected by local (site‐level) grassland management: fertilisation and too low, too high and/or too homogenous intensity of mowing and grazing lead to plant communities with fewer flowers available for pollinators (Dicks et al ., 2020; Franzén & Nilsson, 2008; Johansen et al ., 2019; Sjödin, Bengtsson & Ekbom, 2008; Tadey, 2015). Management may also affect the availability of nesting sites for bees, e.g.…”
Section: Landscape‐scale Land‐use Effects On Pollinators In Grasslandsmentioning
confidence: 99%